PENGARUH KUALITAS PELAYANAN DAN KUALITAS AIR TERHADAP KEPUASAN PELANGGAN PADA PDAM TIRTANADI CABANG TUASAN MEDAN - Hanifah Jasin; Ika Sriwahyuni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Service is how far the difference between reality and expectations of the customer for the services they receive. Quality of care can be determined by comparing the perceptions of customers for services with the services they receive. The product quality is the level of characteristics that can be measured the extent to which a product or service to meet the tastes and needs of consumers. Consumer satisfaction can be created if the goods or services can reach or exceed what customers expect. From the above definition it can be seen the role of service and quality of products is very necessary for the company to give satisfaction to the consumer so that the company in the eyes of the company. So it can be concluded that the quality of service that is effective and excellent product quality to provide customer satisfaction.This study aims to determine how much influence the quality of service and water quality to customer satisfaction of PDAM Tirtanadi Branch Tuasan Medan. The population in this study are all customers of PDAM Tirtanadi Branch Tuasan Medan. And the sample in this study is limited only 101 subscribers of PDAM Tirtanadi Branch Tuasan Medan.Data collection techniques in this study is a list of questions (questionnaire) and study documentation of PDAM Tirtanadi Branch Tuasan Medan. And data analysis techniques used are simple correlation, t-test coefficients f and simple.From the results of the simple correlation is known that the correlation coefficient obtained from the quality of service is 0.199. It shows the influence of service quality on customer satisfaction. Then the correlation coefficient obtained from the water quality is 0.226. It shows the influence of water quality on customer satisfaction. Then the existence of a significant effect between service quality and water quality to customer satisfaction of PDAM Tirtanadi Branch Tuasan Medan. Based on the values obtained significant F test sig. 0.009 ( sig. 0.009 > α 0.05 ), thus H0 accepted. With the conclusion of the existence of a significant effect between service quality and water quality to customer satisfaction of PDAM Tirtanadi Branch Tuasan Medan.